Survey Tingkat Minat Siswa Terhadap Pembelajaran Renang pada Masa Pandemi di SMPN 1 Majalaya - Ahmad Sopian, Roni Mandagini; Gustiawati, Resty (Jurnal Literasi Olahraga, 2022)
The purpose of this study was to determine the level of student interest in swimming lessons during the pandemic. The type of method used is the survey method. The population in this study were seventh grade students of SMPN 1 Majalaya. The subjects used in this study were 100 class VII people. Data collection techniques with a questionnaire (questionnaire). The results showed that the level of student interest in learning swimming at SMPN 1 Majalaya was in the LESS category with a percentage of 55.45%. The level of intrinsic interest with sub-indicators which include Belief, Desire, and Self-confidence has a percentage of 54.84% in the LESS category. For the level of extrinsic interest with sub-indicators which include Environment, Family, and Association has a percentage of 55.98% in LESS.